A Decline in Aminotransferase Activity Due to Lifestyle Modification in Children with NAFLD - Pawel Malecki; Anna Mania; Katarzyna Mazur-Melewska; Wojciech Sluzewski; Magdalena Figlerowicz (Galenos Yayinevi, 2021)
Aim:As obesity rates in children and adolescents increase, non-alcoholic fatty liver disease (NAFLD) has become the most common liver disease affecting this organ. This study aimed to evaluate the effectiveness of lifestyle modifications as a method of improving liver function indexes in children with NAFLD.Materials and Methods:The study group consisted of 49 patients with NAFLD (35 boys and 14 girls), age range 3-16 years (mean 10.51±3.18 years). Anthropometric measurements were taken and laboratory tests were performed. Features of steatosis of the liver were evaluated by ultrasound. The mean follow-up period was 2.45±1.45 years. Aspartate aminotransferase (AST) to [Platelet (PLT) Ratio and Pediatric NAFLD Fibrosis Score (PNFS)] were calculated. The Mediterranean diet and physical exercises were recommended. End-point parameters were a decrease in the aminotransferase level and body weight.Results:In the study group, 35 children (71.43%) were obese, and 7 (14.29%) were overweight. In 22/49 cases (44.9%) body mass index (BMI) loss was achieved, in the other patients, BMI gain was noted. Abnormal alanine aminotransferase (ALT) levels were observed in 25/49 children. In the group of children with initial increased ALT levels, significant reduction of ALT, AST and gamma-glutamyltransferase (GGT) levels were found with regard to baseline values. There was also a significant decline in mean AST to PLT Ratio index (APRI) level and PLT count. Moreover, a decrease in ALT level was negatively related to PNFS, APRI and GGT.Conclusion:Lifestyle modification leads to a significant decrease in aminotransferase levels, even in children who fail to achieve BMI reduction.